Legal regulation of economic functions of the state in the conditions of modern market reforms - Свиридюк, Наталія Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article examines the nature and content of government regulation, including state regulation of economic functions of the state in modern market reforms. The author studies the current problems of legal regulation in the modern market reforms. Also the author analyzes the state budget of Ukraine as the main financial and legal state document. The author emphasizes the adoption of inefficient laws of the State Budget of Ukraine indicates imperfect budget process, the lack of a proper legal mechanism implementing civilized relations between the Parliament and the Cabinet of Ministers of Ukraine, and between parliamentary factions, even between individual MPs and the government. Also the author emphasizes a special role in the economic function of the democratic, social, rule of law given to solving the problem of ordering and legitimization of ownership, including privatization, nationalization, returning to the state property misappropriated state property. The attention is paid to objective necessity in the formation of a stable and stimulating tax laws, and therefore establish a legal basis for the rise of entrepreneurial initiatives of citizens, the activities of economic entities, involving the economy of domestic and foreign investors. Today the current legislation of Ukraine requires some changes in order to streamline the existing rules governing relations in the sphere of legal regulation of economic relations.